EFFECT OF ECOTOURISM ON PLANT DIVERSITY, SOIL AGGREGATE STABILITY AND PARTICULATE ORGANIC MATTER IN NATIONAL KHOJIR PARK IN TEHRAN - Jirdashtani, A.; Ramezani, M.; Nahibi, S.; Khorasani, N. (Annali di Botanica, 2022)
This work assesses the effects of ecotourism on biodiversity, soil POM and ASI in a semi-arid region in Iran. Three zones as High-pressure (0 to 50 m from the road, visitors density: > 20 persons ha-1 day-1), Mid-pressure (50 to 100 m from the road, visitors density: 5-20 persons ha-1 day-1), and Low-pressure (100 to 150 m from the road, visitors density: < 5 persons ha-1 day-1) ecotourism were selected. Indicators of biodiversity, richness, and evenness (0.77, 5.55, and 0.79, respectively) were significantly higher in the High-pressure zone. Soil bulk density (1.95 g m3 ), pH (7.98), and EC (0.82 ds m-1) were significantly higher in the High zone whereas a higher content of total C (0.39%), total N (0.13%), available P (4.83 mg kg-1), available K (3.21 mg kg-1), available Ca (34.91 mg kg-1), and available Mg (5.66 mg kg-1) were found in the Low-pressure zone. POM-C and POM-N were significantly followed by Low (0.21 and 0.03 g kg-1) > Mid (0.14 and 0.02 g kg-1) > High (0.08 and 0.01 g kg-1) zones, respectively. The Low-pressure zone with a population density of only 5 people per ha is associated with enhanced soil biodiversity and nutrient cycles.